Religious Ideology and Clientelist Linkage in the Middle East and North Africa - Shulei Hu; Jingyi Wang; Xiaojin Zhang (Religions, 2024)
The literature on clientelism, the informal exchange of benefits for political support, has proliferated over the last three decades. However, the existing literature largely ignores the role of religion in shaping clientelism in contemporary politics. In particular, few attempts have been made to explore the relationship between religious ideology and clientelism at the party level: How does political parties’ religious ideology impact their clientelist linkages with citizens? This study uses cross-national data of parties in the Middle East and North Africa (MENA) from the V-Party database (1970–2019) to answer this question. Our findings reveal that religious parties are more clientelist than secular parties in the MENA. Particularly, parties’ ties with social organizations mediate the relationship between religious ideology and clientelism. This study extends the literature on the impact of religion on informal political institutions by focusing on the ideology and linkage strategy of political parties in the MENA.